2019
DOI: 10.1371/journal.pone.0210081
|View full text |Cite|
|
Sign up to set email alerts
|

Invasive pneumococcal diseases in children and adults before and after introduction of the 10-valent pneumococcal conjugate vaccine into the Austrian national immunization program

Abstract: BackgroundIn February 2012 the ten-valent pneumococcal conjugate vaccine (PCV10) with a 2+1 doses schedule (3, 5, 12 or 14 months of age) without catch-up vaccination was introduced in Austria. We assessed direct and indirect vaccine effects on invasive pneumococcal disease (IPD) by a population-based intervention study.MethodsThe study period was divided into pre- (2009–2011) and post-period (2013–2017, February), regarding 2012 as transition year. Outcomes were defined as PCV10 ST-IPD, the PCV10-related ST 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 48 publications
2
21
0
4
Order By: Relevance
“…Because the more broadly vaccinations are implemented, the stronger both individual immunity and herd immunity becomes, the greater the benefits for everyone. Indeed, every study that has been done of the economic impact of pneumococcal and Hib vaccination programs has shown that for every billion dollars invested in vaccination, several billions are saved in critical care costs for elderly and atrisk patients (Wateska, et al, 2020;Richter, et al, 2019;Zhang, et al, 2018;Ciruela, et al, 2018;Baldo, et al, 2016;Arencibia Jiménez, et al, 2014;Isaacman, et al, 2008 ). Actual savings may be significantly greater since these economic studies have not included the benefits that may accrue from protection against the global economic devastation that a coronavirus or influenza pandemic can cause by shutting down businesses and harming trade.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Because the more broadly vaccinations are implemented, the stronger both individual immunity and herd immunity becomes, the greater the benefits for everyone. Indeed, every study that has been done of the economic impact of pneumococcal and Hib vaccination programs has shown that for every billion dollars invested in vaccination, several billions are saved in critical care costs for elderly and atrisk patients (Wateska, et al, 2020;Richter, et al, 2019;Zhang, et al, 2018;Ciruela, et al, 2018;Baldo, et al, 2016;Arencibia Jiménez, et al, 2014;Isaacman, et al, 2008 ). Actual savings may be significantly greater since these economic studies have not included the benefits that may accrue from protection against the global economic devastation that a coronavirus or influenza pandemic can cause by shutting down businesses and harming trade.…”
Section: Resultsmentioning
confidence: 99%
“…The data presented in TABLE 1 suggest that countries with high COVID-19 death rates tend to have low childhood vaccination rates for pneumococci. Hib and pneumococcal vaccines are strong determinants of herd immunity protecting at-risk adults and the elderly from pneumonia risk (Lexau, et al, 2005;Isaacman, et al, 2008;Pletz, et al, 2016;Richter, et al, 2019;Wiese, et al, 2019). In a few countries, high levels of infant vaccination with PCV-13 seem to balance out low levels of adult vaccination, as exemplified by the case of the Netherlands and Switzerland (TABLE 1).…”
Section: Hib Is Haemophilus Influenzae Type B Vaccine; Bcg Is Bacillumentioning
confidence: 99%
See 1 more Smart Citation
“…Eine Metaanalyse zeigt anhand von Daten aus den USA, Europa und Australien, dass die IPD der im Impfstoff enthaltenen Serotypen bei Erwachsenen nach Einführung des 7-valenten Pneumokokkenimpfstoffes (PCV7) durchschnittlich um 90 % gesunken sind [21]. Der Rückgang der Inzidenz der im Impfstoff enthaltenen Serogruppen bezieht sich sowohl auf geimpfte als auch ungeimpfte Personen und ist auch bei PCV10 und PCV13 in ähnlicher Weise zu beobachten [21][22][23].…”
Section: Pneumokokken -Impfempfehlungen Und Impfstoffeunclassified
“…Relativ rasch nach Einführung des PCV7 war allerdings ein Replacement durch nicht im Impfstoff enthaltene Serotypen zu beobachten [24,25]. Durch diese Serotypen werden aktuell vermehrt IPDs verursacht, wie bereits erwähnt [18,23,26,27].…”
Section: Pneumokokken -Impfempfehlungen Und Impfstoffeunclassified